2015
DOI: 10.1155/2015/804385
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the Formation of New Semantics: MVPA Investigation of Rapid Neocortical Plasticity during Associative Encoding through Fast Mapping

Abstract: Neocortical structures typically only support slow acquisition of declarative memory; however, learning through fast mapping may facilitate rapid learning-induced cortical plasticity and hippocampal-independent integration of novel associations into existing semantic networks. During fast mapping the meaning of new words and concepts is inferred, and durable novel associations are incidentally formed, a process thought to support early childhood's exuberant learning. The anterior temporal lobe, a cortical sema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 107 publications
(159 reference statements)
7
43
1
Order By: Relevance
“…Compared to the EE condition, the FM condition had significantly increased activity in the anterior temporal lobe (ATL). This finding, in concert with a similar study (Atir-Sharon et al, 2015) suggests that an ATL-related network is responsible for associations learned through FM. In total, these studies provide a potential alternative learning strategy for novel arbitrary associations mediated by the ATL.…”
Section: Introductionsupporting
confidence: 86%
“…Compared to the EE condition, the FM condition had significantly increased activity in the anterior temporal lobe (ATL). This finding, in concert with a similar study (Atir-Sharon et al, 2015) suggests that an ATL-related network is responsible for associations learned through FM. In total, these studies provide a potential alternative learning strategy for novel arbitrary associations mediated by the ATL.…”
Section: Introductionsupporting
confidence: 86%
“…On this topic, Sharon et al (2011) reported one case (patient K.S.) with relatively focal left temporal pole damage who had word learning impairments despite fast-mapping study, and functional neuroimaging studies have provided correlational evidence consistent with that perspective (Atir-Sharon et al, 2015; Merhav et al, 2015). Returning to the current patient sample, the history of epilepsy shared by all TL participants could potentially have contributed to deficits in name learning.…”
Section: 1 Discussionmentioning
confidence: 91%
“…The large number of component processes will make it challenging to identify regions that might be uniquely associated with and necessary for fast-mapping behavior. Candidate regions might be identified based on correlational functional neuroimaging data related to word learning and fast mapping performance (Atir-Sharon, Gilboa, Hazan, Koilis, & Manevitz, 2015; Davis et al, 2009; Merhav, Karni, & Gilboa, 2015), and those candidate regions could be evaluated neuropsychologically.…”
Section: 1 Discussionmentioning
confidence: 99%
“…However, there are studies in which these criteria were entirely fulfilled but still, no 1 This does not necessarily mean that learning by means of FM is always hippocampus-independent. It has been shown that the hippocampus contributes to FM learning in healthy young adults (Atir-Sharon, Gilboa, Hazan, Koilis, & Manevitz, 2015) or at least it cannot finally be excluded that it is not involved (Merhav et al, 2015). We propose that in patients with severe and selective hippocampal lesions it is valid to conclude that hippocampal activity cannot have contributed to FM learning or retrieval.…”
mentioning
confidence: 74%
“…Contrary to previous studies (cf. Atir- Sharon et al, 2015;Coutanche & Thompson-Schill, 2014;Greve et al, 2014;Himmer et al, 2017;Korenic et al, 2016;Merhav et al, 2014Merhav et al, , 2015Sharon et al, 2011;Smith et al, 2014;Warren & Duff, 2014;Warren et al, 2016), the EE group was presented with the same questions as the FM groups, in order to prevent any confounds due to inconsistencies in task demands apart from the critical FM determinants. Before the actual experiment started, all three groups conducted a practice phase of six encoding trials.…”
Section: Design and Proceduresmentioning
confidence: 99%